2013
DOI: 10.6061/clinics/2013(01)oa03
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns in Brazilian patients with non-alcoholic fatty liver disease: a cross-sectional study

Abstract: OBJECTIVE:Recent evidence suggests that non-alcoholic fatty liver disease is associated with diet. Our aim was to investigate the dietary patterns of a Brazilian population with this condition and compare them with the recommended diet.METHODS:A cross-sectional study was conducted on 96 non-alcoholic fatty liver disease patients before any dietetic counseling. All patients underwent abdominal ultrasound, biochemical tests, dietary evaluations, and anthropometric evaluations. Their food intake was assessed by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
4
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 37 publications
7
29
4
4
Order By: Relevance
“…In a study in rats, supplementation of vitamin B6 (1 mg per animal, daily) to a hyperlipidemic diet significantly suppressed increase of body weight, degree of fat deposition in liver, and serum level of cholesterol compared to the conditions of an ordinary diet and the hyperlipidemic diet alone in 14 days observation period [181]. A recent cross sectional study indicates that daily intake of the calcium, sodium, potassium, vitamins B6 and C did not meet the recommended values in most NAFLD patients [182]. Therefore, these findings suggest that the inadequacy of vitamin B6 is a potential “hit” in the progress of NAFLD.…”
Section: Non-alcoholic Fatty Liver Disease (Nafld) and Periapical mentioning
confidence: 99%
“…In a study in rats, supplementation of vitamin B6 (1 mg per animal, daily) to a hyperlipidemic diet significantly suppressed increase of body weight, degree of fat deposition in liver, and serum level of cholesterol compared to the conditions of an ordinary diet and the hyperlipidemic diet alone in 14 days observation period [181]. A recent cross sectional study indicates that daily intake of the calcium, sodium, potassium, vitamins B6 and C did not meet the recommended values in most NAFLD patients [182]. Therefore, these findings suggest that the inadequacy of vitamin B6 is a potential “hit” in the progress of NAFLD.…”
Section: Non-alcoholic Fatty Liver Disease (Nafld) and Periapical mentioning
confidence: 99%
“…Dietary carbohydrate especially sugars contribute to increased circulating insulin and triglyceride concentrations and lead to increased hepatic de novo lipogenesis and decreased hepatic insulin sensitivity because of the lipogenic potential of fructose during liver metabolism. [12][13][14][15][16] In addition, recent genome-wide studies have identified several polymorphisms that contribute to increased liver fat accumulation, with some of these genes relating to dietary carbohydrate and sugar consumption. 7,33 Dietary fructose consumption primarily in the form of soft drinks worldwide has increased in parallel with the increase in obesity, diabetes, and NAFLD, and some studies have suggested a direct association.…”
Section: Influence Of Macronutrients On Nafldmentioning
confidence: 99%
“…Estudo piloto realizado por Rocha et al 45 sugere que a utilização de fibras solúveis pode colaborar no controle tanto de fatores de risco quanto das enzimas hepáticas em pacientes com DHGNA. Em outra pesquisa desenvolvida no Brasil com 96 portadores de DHGNA sem intervenção nutricional, resultados semelhantes aos obtidos neste estudo foram relatados, ou seja, consumo deficiente de ácidos graxos insaturados, fibras e vitaminas e elevada ingestão de saturados e colesterol 46 .…”
Section: (H)unclassified